The Ultimate book of top 10 lists a mind-boggling collection of fun, fascinating and bizarre facts on movies, music, sports, crime, celebrities, history, trivia and more : the best of listverse.com - Frater, Jamie (Ulysses Press, 2010)
From crime, movies and music to science, history and literature this book offers and incredible array of intriguing top 10 lists, including: urban legends-debunked, influential people never lived, ancient methods of execution, poisonous food we love to it, inventions of the middle ages, gruesome fairytale origins, secret societies, amazing film sword flights, bizarre animal mating rituals, misconceptions about evolution, tips for frugal living, fascinating graveyards you must see.